Nepal Earthquake 25 April 2015: Hydro projects damaged, risks and lessons learned for design considerations - Sunuwar, Subas Chandra (Journal of Nepal Geological Society, 2018)
The 25 April 2015 Nepal earthquake of magnitude 7.8 epicentre at Gorkha and magnitude 7.3 aftershocks on 12 May epicentre at Dolakha had devastating impacts on 14 districts including Kathmandu, capital city of Nepal. Death toll was nearly 9,000 and hundreds of thousands of inhabitants became homeless. The earthquake severely damaged mainly surface structures of hydro projects, access roads, clay mortar stone masonry houses and structurally weak concrete houses. Landslides, rock falls, debris flow, liquefaction, river damming, Landslides Dammed Outburst Flood (LDOF) and Glacial Lake Outburst Flood (GLOF) are expected earthquake-induced hazards. However, landslides and grounds shaking were responsible for major damaged. A total of 15 hydro projects in operations and under construction were affected by the earthquake. In hydro projects damages were recorded in surface structures such as power house, settling basin, penstock pipes, and diversion weir constructed at base of steep terrains. For instance, surface penstock pipe, lying at base of rock cliff, of running 40 MW Upper Bhote Koshi Project was ruptured by rock falls and as a result flooded surface powerhouse located downstream by water from penstock and headrace tunnel. Similarly, diversion weir, surface settling basin and headrace penstock pipe of running 5 MW Mialung Project were also severely damaged by slides and rock falls. On the other hand, only minor cracking of sprayed concrete at corners and protruded edges in underground structures were observed. In hydro projects, there is a practice of considering seismic load in design of structures but the effects of earthquake induced hazards were not foreseen. This devastating earthquake gave good lessons for design considerations of hydro projects in future. This article summarises earthquake damage, risks and lessons learned for Hydro projects in Nepal.